Evaluating Optimal Treatment for Melanoma: A Network Meta-Analysis - Mengyuan ZHANG; Qiong HE; Yuifang YU; Baolin ZHANG (Chinese Journal of Plastic and Reconstructive Surgery, 2021)
ABSTRACT: Background: It is necessary to determine the optimal treatment for melanoma as the incidence of melanoma is increasing every year. In this study, we conducted a meta-analysis to compare the effectiveness of available treatments for melanoma. Methods: The index keywords “melanoma” and “treatment” were used to search the PubMed, Cochrane Library, Web of Science, and Embase databases, and the articles were limited to randomized controlled trials. The search was filtered for articles published until February 2020, and articles were independently extracted by two reviewers. Network meta-analysis (Stata® 14.0 software network package, Stata Corp LLC TX, USA) was used to compare the effectiveness of the mentioned treatments of melanoma. Results: A total of 616 articles were screened of which 6 were selected for meta-analysis, involving 5 treatment measures and 2 047 patients (those who were not followed up on were excluded). The treatment strategies reported for melanoma included tumor necrosis factor (L19-TNFα) and interleukin-2 (L19IL2) in combination with dacarbazine (L19IL2 + DTIC), DTIC, programmed cell death-1 plus cytotoxic T cell antigen-4 (PD-1 + CTLA-4), PD-1, and CTLA-4. Conclusion: Among L19IL2 + DTIC, DTIC, PD-1 + CTLA-4, PD-1, and CTLA-4, CTLA-4 is found to be the best treatment method for melanoma. Our study findings provide a reference for the clinical treatment of melanoma and can clarify the direction for setting up controlled clinical trials.